⎩ ⎪ ⎨ ⎪ ⎧ a + b + c = 1 a 2 + b 2 + c 2 = 2 2 a 3 + b 3 + c 3 = 3 2
Given that a , b and c are complex numbers satisfying the system of equations above. If the value of a 3 1 + b 3 1 + c 3 1 is equal to q p , where p and q are coprime positive integers, find p + q .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Learned a new way to think . Thanks !😀😀
Let
a
,
b
,
c
be the roots of the cubic equation with symmetric sums
S
1
,
S
2
,
S
3
.
Let
P
n
=
a
n
+
b
n
+
c
n
According to Newton's Identities,
P
1
=
S
1
P
2
=
S
1
P
1
−
2
S
2
P
3
=
S
1
P
2
−
S
2
P
1
+
3
S
3
Solving these equations for
S
1
,
S
2
,
S
3
yields
S
1
=
1
,
S
2
=
2
−
3
,
S
3
=
6
7
Therefore, the cubic equation with roots
a
,
b
,
c
as roots is given by
x
3
−
S
1
x
2
+
S
2
x
−
S
3
=
0
Substituting the values of
S
1
,
S
2
,
S
3
∴
6
x
3
−
6
x
3
−
9
x
−
7
=
0
Thus, the equation whose roots are reciprocal of the given equation are given by substituting
x
=
y
1
New equation :
7
x
3
+
9
x
2
+
6
x
−
6
=
0
Let the symmetric sums of this new equation be denoted by
e
1
,
e
2
,
e
3
By Vieta's formula,
e
1
=
7
−
9
e
2
=
7
6
e
3
=
7
−
6
Applying Newton's Identities again,
P
1
′
=
e
1
=
7
−
9
P
2
′
=
e
1
P
1
′
−
2
e
2
=
4
9
8
1
−
2
×
7
6
=
4
9
−
3
P
3
′
=
e
1
P
2
′
−
e
2
P
1
′
+
3
e
3
=
3
4
3
2
7
+
4
9
5
4
+
7
1
8
=
3
4
3
2
7
+
3
7
8
+
8
8
2
=
3
4
3
1
2
8
7
M
=
a
3
1
+
b
3
1
+
c
3
1
=
P
3
′
=
3
4
3
1
2
8
7
Comparing we get,
p
=
1
2
8
7
,
q
=
3
4
3
p
+
q
=
1
2
8
7
+
3
4
3
=
1
6
3
0
I also did this way!!😀😀
Problem Loading...
Note Loading...
Set Loading...
a + b + c = 1 ..... ( 1 )
a 2 + b 2 + c 2 = 4 ...... ( 2 )
a 3 + b 3 + c 3 = 9 ...... ( 3 )
Squring both sides to ( 1 ) .
⇒ a 2 + b 2 + c 2 + 2 ( a b + b c + c a ) = 1
⇒ ( a b + b c + c a ) = 2 − 3
Adding ( − 3 a b c ) both sides to ( 3 ) .
⇒ a 3 + b 3 + c 3 − 3 a b c = 9 − 3 a b c
⇒ ( a b c ) = 6 7 ..... ( 4 )
⇒ a 3 1 + b 3 1 + c 3 1 = ( a b c ) 3 ( a b ) 3 + ( b c ) 3 + ( c a ) 3
Now, finding ( a b ) 3 + ( b c ) 3 + ( c a ) 3 .
Let a b = x , b c = y and c a = z .
⇒ x 3 + y 3 + z 3 = f
Adding ( − 3 x y z ) both sides.
⇒ ( x + y + z ) ( x 2 + y 2 + z 2 − ( x y + y z + z x ) = f − 3 x y z
⇒ ( a b + b c + c a ) [ ( a b + b c + c a ) 2 − 3 a b c ( a + b + c ) ] = f − 3 ( a b c ) 2
⇒ ( 2 − 3 ) [ 3 6 4 9 − 6 2 1 ] = f − 1 2 4 9
⇒ ( a b ) 3 + ( b c ) 3 + ( c a ) 3 = 2 4 1 4 3 .... ( 5 )
⇒ ( a b c ) 3 ( a b ) 3 + ( b c ) 3 + ( c a ) 3
Now putting values from ( 4 ) and ( 5 ) .
⇒ 2 4 1 4 3 × ( 6 ) 3 ( 7 ) 3
⇒ 8 2 3 2 3 0 8 8 8 = 3 4 3 1 2 8 7
⇒ 3 4 3 1 2 8 7 = q p
⇒ p + q = 1 2 8 7 + 3 4 3 = 1 6 3 0 .